CAR T Cells for Acute Myeloid Leukemia: State of the Art and Future Directions - Mardiana, Sherly; Gill, Saar (Frontiers in Oncology, 2020)
Relapse after conventional chemotherapy remains a major problem in patients with myeloid malignancies such as acute myeloid leukemia (AML), and the major cause of death after diagnosis of AML is from relapsed disease. The only potentially curative treatment option currently available is allogeneic hematopoietic stem cell transplantation (allo-HSCT), which through its graft-vs.-leukemia effects has the ability to eliminate residual leukemia cells. Despite its long history of success however, relapse following allo-HSCT is still a major challenge and is associated with poor prognosis. In the field of adoptive therapy, CD19-targeted chimeric antigen receptor (CAR) T cells have yielded remarkable clinical success in certain types of B-cell malignancies, and substantial efforts aimed at translating this success to myeloid malignancies are currently underway. While complete ablation of CD19-expressing B cells, both cancerous and healthy, is clinically tolerated, the primary challenge limiting the use of CAR T cells in myeloid malignancies is the absence of a dispensable antigen, as myeloid antigens are often co-expressed on normal hematopoietic stem/progenitor cells (HSPCs), depletion of which would lead to intolerable myeloablation. This review provides a discussion on the current state of CAR T cell therapy in myeloid malignancies, limitations for clinical translation, as well as the most recent approaches to overcome these barriers, through various genetic modification and combinatorial strategies in an attempt to make CAR T cell therapy a safe and viable option for patients with myeloid malignancies.